The Effectiveness of Matific Interactive Game Media to Improve Mathematics Learning Outcomes of Grade VII Students on the Matter of Integers - Romita, Rahtu Dila; Prastika, Rahayu; Putri, Rosa Riswana; Hafizhah, Ummul; Tasman, Fridgo (Jurnal Basicedu, 2024)
Math learning is often considered difficult by students, this requires the creativity of math teachers to innovate, one of which is by using interactive learning media such as Matific. The purpose of this study was to determine whether or not the use of Matific interactive game media was effective in improving the learning outcomes of seventh grade mathematics students at SMP Negeri 7 Padang on integer material. This study uses a qualitative method by giving a questionnaire. The results of the research on the use of interactive game media Matific has been running effectively in learning mathematics, especially integers and is able to improve student learning outcomes. This is evidenced by the percentage of student questionnaire assessment results of 88.45% which means that Matific games are very effective as interactive learning media. This research contributes to the field of education in developing mathematics skills, increasing student engagement, and reducing student anxiety through educational games that utilize technology in the teaching and learning process. Student involvement in the mathematics learning process is related to increased student learning outcomes. For this reason, it is hoped that mathematics will no longer be considered a difficult lesson by students